Answer:
( x-6)^2 -17
Explanation:
X^2 - 12x + 19
we need it in given below form
(x + a)^2 + b
we know that
![(x + a)^2 = x^2 + 2ax + a^2\\](https://img.qammunity.org/2021/formulas/mathematics/middle-school/slmr6hbpqgxueheidz8vnc0izw67vhtzhp.png)
lets convert that in same form
X^2 - 12x + 19 = x^2 + 2(-6)x + 19
comparing x^2 + 2(-6)x to x^2 + 2ax
we have a -6
now
(x-6)^2 = x^2 + 2(-6)x + 36
36 is missing in the x^2 + 2(-6)x + 19 hence to get that
we add and subtract 36 in the above equation
so we have
x^2 + 2(-6)x + 19 + 36 -36
rearranging it \
(x^2 + 2(-6)x + 36) -36 + 19 (x^2 + 2(-6)x + 36 =( x-6)^2)
=>( x-6)^2 -17
comparing the above equation to
(x + a)^2 + b
we have a = -6
b = -17
( x-6)^2 -17